HYPERKALEMIA RISK COMPARISON IN PATIENTS ON VALSARTAN/SACUBITRIL: NORMAL RENAL PROFILE VERSUS ADVANCED CHRONIC KIDNEY DISEASE (The Research of Medical Science Review, 2025)
Objective: This study aimed to compare the risk of hyperkalemia in patients receiving sacubitril/valsartan therapy, focusing on differences between those with normal renal function and those with advanced chronic kidney disease (CKD).Methods: A retrospective cohort analysis was conducted on 150 heart failure patients with reduced ejection fraction (HFrEF), divided equally into two groups based on estimated glomerular filtration rate (eGFR): normal renal function (eGFR ≥ 60 mL/min/1.73 m²) and advanced CKD (eGFR < 30 mL/min/1.73 m²). Hyperkalemia incidence, severity, and treatment discontinuation rates were assessed using electronic health records. Statistical analyses included Chi-square tests, Kaplan-Meier curves, and Cox proportional hazards models.Results: The advanced CKD group exhibited a significantly higher incidence of hyperkalemia (29.3% vs. 10.7%, *p*=0.005), with severe cases (>6.5 mmol/L) occurring exclusively in this cohort. These patients also faced a 3.2-fold increased hazard of hyperkalemia (HR: 3.2, 95% CI: 1.4–7.1) and higher treatment discontinuation rates (12% vs. 2.7%, *p*=0.03).Conclusion: Sacubitril/valsartan therapy is associated with a markedly elevated risk of hyperkalemia in advanced CKD patients, necessitating rigorous potassium monitoring and careful clinical management in this population.